Pengaruh Inflasi, Currency Exchange, dan BI Rate terhadap Pembiayaan Murabahah di Bank BRI Syariah Tahun 2015-2020 - Nadya Anathasya Cristine Br. Tambun; Nana Diana (Journal on Education, 2023)
The purpose of this research is to identify the impact relationship between change of inflation, currency exchange fluctuation of Indonesian Rupiah exchange against foreign currencies, and the provisions for determining BI rate by Bank Indonesia for murabahah financing carried out by one of the Islamic banks in Indonesia. Financial Statements of Bank BRI Syariah is the population that used for this research. The data collected for this research is secondary data derived from information published on the official websites of the OJK and BPS. The type of analysis used in this study is a type of multiple linear regression analysis using time series data type. Result from this research is indicate that inflation, currency exchange rates, and the BI rate do not have a significant effect on murabahah financing at Bank BRI Syariah in the period 2015 to 2020.